No Consistent Evidence for Microbiota in Murine Placental and Fetal Tissues - Kevin R. Theis (American Society for Microbiology, 2020)
ABSTRACT The existence of a placental microbiota and in utero colonization of the fetus have been the subjects of recent debate. The objective of this study was to determine whether the placental and fetal tissues of mice harbor bacterial communities. Bacterial profiles of the placenta and fetal brain, lung, liver, and intestine samples were characterized through culture, quantitative real-time PCR (qPCR), and 16S rRNA gene sequencing. These profiles were compared to those of the maternal mouth, lung, liver, uterus, cervix, vagina, and intestine, as well as to background technical controls. Positive bacterial cultures from placental and fetal tissue samples were rare; of the 165 total bacterial cultures of placental tissue samples from the 11 mice included in this study, only nine yielded at least a single colony, and five of those nine positive cultures came from a single mouse. Cultures of fetal intestinal tissue samples yielded just a single bacterial isolate, Staphylococcus hominis, a common skin bacterium. Bacterial loads of placental and fetal brain, lung, liver, and intestinal tissues were not higher than those of DNA contamination controls and did not yield substantive 16S rRNA gene sequencing libraries. From all placental or fetal tissue samples (n = 51), there was only a single bacterial isolate that came from a fetal brain sample having a bacterial load higher than that of contamination controls and that was identified in sequence-based surveys of at least one of its corresponding maternal samples. Therefore, using multiple modes of microbiological inquiry, there was not consistent evidence of bacterial communities in the placental and fetal tissues of mice. IMPORTANCE The prevailing paradigm in obstetrics has been the sterile womb hypothesis, which posits that fetuses are first colonized by microorganisms during the delivery process. However, some are now suggesting that fetuses are consistently colonized in utero by microorganisms from microbial communities that inhabit the placenta and intra-amniotic environment. Given the established causal role of microbial invasion of the amniotic cavity (i.e., intra-amniotic infection) in pregnancy complications, especially preterm birth, if the in utero colonization hypothesis were true, there are several aspects of current understanding that will need to be reconsidered; these aspects include the magnitude of intra-amniotic microbial load required to cause disease and its potential influence on the ontogeny of the immune system. However, acceptance of the in utero colonization hypothesis is premature. Herein, we do not find consistent evidence for placental and fetal microbiota in mice using culture, qPCR, and DNA sequencing.